The Effectiveness of The Integrated Service Center for Women and Children Empowerment (P2TP2A) Child Abuse Hotline - Devina Nabila Utama; Yanto Heryanto (Universitas Muhammadiyah Gorontalo, 2026)
Child abuse is still a serious public problem in Indonesia that requires public services that are accessible, responsive, and effective in providing immediate protection for victims. The Cirebon Regency Integrated Service Center for Women and Children Empowerment (P2TP2A) hotline is the first contact point in reporting child abuse cases and has an important role in facilitating timely intervention and referral services.This study aims to review the effectiveness of the P2TP2A hotline service in dealing with child abuse cases through analysis of service processes, human resources, supporting facilities, and public trust. The research employed a qualitative descriptive method, which was supported by descriptive quantitative data. Data were collected by means of interviews with P2TP2A officers and questionnaires distributed to 28 service users. The analysis was based on the organizational effectiveness theory of Richard M. Steers, which includes goal attainment, integration, and adaptation. The results indicate that the hotline service is effective in general. The service procedures are easy to understand, the responses are provided within a maximum of 24 hours, and the staff show competence, professionalism, and effective coordination with related institutions. Supporting facilities like the Siaga Katon 112 system and digital reporting services have improved public access. However, there are challenges, especially limited human resources and the need to strengthen the complaint management system to ensure consistent service quality. In summary, Cirebon Regency's P2TP2A hotline has successfully handled child abuse reports, but human resource capacity, complaint resolution, and ongoing service evaluation must improve to sustain and improve child protection services.